Analyzing the Effectiveness of Virtual Reality and Augmented Reality in Vocational Practicum to Enhance SMK Students' Competency in the VUCA Era - Fiskia Rera Baharuddin; Amiruddin; Nurlaela (Jurnal MEKOM (Media Komunikasi Pendidikan Kejuruan), 2026)
Purpose - This study investigates the effectiveness of Virtual Reality (VR) and Augmented Reality (AR) in enhancing vocational competencies among SMK students in the VUCA era. It applies the Technology Acceptance Model (TAM) to examine students’ acceptance of immersive learning technologies. Methods - A quantitative design with a pretest-posttest control group was used involving 200 SMK students from technical programs. The study employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze the effects of Perceived Usefulness, Perceived Ease of Use, Attitude Toward Using, Behavioral Intention, and User Satisfaction. Findings - The findings show that Perceived Ease of Use significantly affects Perceived Usefulness, Attitude Toward Using, Behavioral Intention, and User Satisfaction. This confirms that ease of use is central to students’ acceptance of VR/AR. Behavioral Intention is the strongest predictor of User Satisfaction, indicating that students’ willingness to continue using VR/AR is closely linked to satisfaction. However, Perceived Usefulness does not significantly influence Attitude Toward Using, suggesting that functional value may be less decisive during early adoption. Research implications - The results highlight the need to design VR/AR learning tools that are user-friendly, engaging, and capable of encouraging continued use. Educators, developers, and policymakers should prioritize usability and behavioral intention when implementing immersive technologies in vocational education.  Originality - This study integrates TAM with immersive learning in vocational education and provides evidence on how VR/AR supports competency development and student engagement in developing contexts.